2019
DOI: 10.1016/j.cophys.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychology of human appetite — understanding the excitatory and inhibitory mechanisms of homeostatic control

Abstract: This is a repository copy of Biopsychology of human appetite -understanding the excitatory and inhibitory mechanisms of homeostatic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
0
9
0
2
Order By: Relevance
“…It links eating motivations and behaviours to cognitive and physiological processes across the three phases. There is an extensive literature on biomarkers of satiation and satiety [ 183 ] and an associated literature on the assessment of satiation and satiety using biological and behavioural measures [ 82 , 150 , 166 , 180 , 181 , 184 , 185 ] as well as brain imaging following exposure to food-related cues [ 169 ].…”
Section: Discussionmentioning
confidence: 99%
“…It links eating motivations and behaviours to cognitive and physiological processes across the three phases. There is an extensive literature on biomarkers of satiation and satiety [ 183 ] and an associated literature on the assessment of satiation and satiety using biological and behavioural measures [ 82 , 150 , 166 , 180 , 181 , 184 , 185 ] as well as brain imaging following exposure to food-related cues [ 169 ].…”
Section: Discussionmentioning
confidence: 99%
“… 43 However, there is a narrow relationship between them, and both are influenced by internal (eg, physiology) and external factors (eg, social and cultural factors). 43 , 44 So, beyond biological processes, what people eat depends on many factors. The determinants of food intake can be grouped into individual factors, social, physical, and macro-level environments, as described by Story et al 45 …”
Section: Ssbs Consumption and Appetitive Behavioursmentioning
confidence: 99%
“…43 However, there is a narrow relationship between them, and both are influenced by internal (eg, physiology) and external factors (eg, social and cultural factors). 43,44 So, beyond biological processes, what people eat depends on many factors. The determinants of food intake can be grouped into individual factors, social, physical, and macro-level environments, as described by Story et al 45 Cross-sectional studies have shown that SSBs consumption is positively associated with food approach behaviours, which are linked to child's general appetite and interest for food and drinks, and negatively with food avoidant behaviours, which represent child's avoidance and lack of interest towards foods.…”
Section: Ssbs Consumption and Appetitive Behavioursmentioning
confidence: 99%
“…The blood supplied to the digestive tract is reduced for use by other organs, including the brain. Because the brain is the most important organ in the thought process, the brain's performance becomes more maximized (Casanova et al, 2019). This will make it easier for students who practice the Dalailul Qur'an fasting in memorizing Holy Qur'an, it is supported again, that the Dalailul Qur'an fasting practitioners are obliged to do wirid, through reading 1 juz (chpater) per day sequentially from chapter 1 to 30 during 30 days ahead, and students recite the Quran every 30 days.…”
Section: The Role Of Dalailul Qur'an Fasting In the Formation Of Shoi...mentioning
confidence: 99%
“…It can be said that students who practice fasting are better able to resist lust and maladaptive behavior. A full stomach will increase the ability of lust in carrying out maladaptive behavior (Casanova et al, 2019). Among the maladaptive behaviors are procrastination, laziness which then leads to destructive gossiping behavior, heavy feeling of doing worship, as well as other unproductive behavior.…”
Section: The Role Of Dalailul Qur'an Fasting In the Formation Of Shoi...mentioning
confidence: 99%